Rhetoric and Creative Thinking - Balkhair, Ahmed; Al-Sayari, Omar (Al-Adab Journal, 2025)
This paper aims to identify the reality of the relationship between rhetoric and the science of creative thinking, in that the rhetoric material represents the process of building the human personality through the formulation of standards and scales that help the person to measure the level of expression of his sense of statement, with its two types of clarity and resolution, and thus rhetoric is the ability On the production and generation of discourse, as they are the criteria for evaluating and interpreting discourse, and distinguishing the good from the best, according to fixed principles, perhaps the most important of which are: the combination of the different genders and the proper composition between them, with the aim of deriving the particulars from the rare, not the cold, meanings, by provoking the details of the minerals of meanings The mysterious lurking in the curves of every soul; This is because every soul carries two kinds of meanings, The first: shared with her other sisters, and the second: the meaning that was created for her, as it is a product of her thoughts. and his feeling; To speak and provoke his instinct, forming a graphic imprint with which he differentiates, establishing this according to the requirements of a psychological mentality that seeks clarity and resolution, understanding and understanding, influence and change, and this is what necessitates that he has a number and types of thinking strategies with his operations and methods to strive in choosing what achieves his purpose.